Nano Online 2016
DOI: 10.1515/nano.bjneah.6.183
|View full text |Cite
|
Sign up to set email alerts
|

NanoE-Tox: New and in-depth database concerning ecotoxicity of nanomaterials

Abstract: The increasing production and use of engineered nanomaterials (ENMs) inevitably results in their higher concentrations in the environment. This may lead to undesirable environmental effects and thus warrants risk assessment. The ecotoxicity testing of a wide variety of ENMs rapidly evolving in the market is costly but also ethically questionable when bioassays with vertebrates are conducted. Therefore, alternative methods, e.g., models for predicting toxicity mechanisms of ENMs based on their physico-chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 122 publications
(169 reference statements)
2
18
0
Order By: Relevance
“…Phytotoxicology of engineered nanomaterials is a comparatively new field of research, which according to Nowack and Bucheli [116] did not exist before 2007. Accordingly, the potential toxicity of nanoparticles on plants has not yet been widely investigated, and the reported results are frequently descriptive and contradictory with very limited information on the underlying modes of action [117]. Physiological processes potentially affected by interactions with nanomaterials comprise alterations of gene expression [118,119], DNA damage [120,121] and increased formation of ROS [122,123].…”
Section: Impact Of Carbon-based Nanomaterials On Plantsmentioning
confidence: 99%
“…Phytotoxicology of engineered nanomaterials is a comparatively new field of research, which according to Nowack and Bucheli [116] did not exist before 2007. Accordingly, the potential toxicity of nanoparticles on plants has not yet been widely investigated, and the reported results are frequently descriptive and contradictory with very limited information on the underlying modes of action [117]. Physiological processes potentially affected by interactions with nanomaterials comprise alterations of gene expression [118,119], DNA damage [120,121] and increased formation of ROS [122,123].…”
Section: Impact Of Carbon-based Nanomaterials On Plantsmentioning
confidence: 99%
“…textiles (Ag), coatings (Ag and CuO), cosmetics (Ag) and pest control (Ag and CuO) entails elevated release potential into waterbodies (Keller et al, 2013;Nowack et al, 2012). Ag and CuO NPs are the most harmful NPs to freshwater biota (Bondarenko et al, 2013a;Juganson et al, 2015) mainly due to the shed Ag-and Cu-ions (Angel et al, 2013;Heinlaan et al, 2008;Jemec et al, 2016;Newton et al, 2013;Notter et al, 2014;Sakamoto et al, 2015). However, it has been suggested that the environmental hazard of ion-releasing metal NPs cannot be directly extrapolated from that of the free metal ion (Blinova et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…According to the NanoE-Tox database (on 224 nanoecotoxicological papers) (Juganson et al, 2015), just 15% of engineered NP toxicity studies have been performed in natural water and in 5% of the studies, natural organic matter has been used as a natural dispersant/coating of the NPs or with an aim to study its influence on NPs' biological effects. This necessitates studies on NP behaviour and toxicity in the natural aquatic environment as under environmentally relevant conditions, acute toxicity of metal formulations may be significantly different compared to the standardized (laboratory) conditions (Handy et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The first five parameters with high relative importance follow the order shown in (1), while the relative importance of the other studied parameters was at least 3 orders of magnitude lower compared to the first fives. [12] k diss > r LSP > ρ SNP > α 2 ≈ Depth water (1) where k diss is the dissolution rate of ENPs in freshwater; r LSP is the radius of larger suspended particles (LSP, > 450 nm) in freshwater; ρ SNP is the density of the suspended particles in freshwater; α 2 is the attachment efficiency between ENPs and LSP; Depth water is the depth of freshwater. [12], [18] C…”
Section: B Sensitivity Analysis Of Fate Modelmentioning
confidence: 99%
“…Ref. [1]- [3] the wastewater treatment plant (WWTP) effluent is the main source of the ENPs in aquatic ecosystems. Ref.…”
Section: Introductionmentioning
confidence: 99%